2019
DOI: 10.1002/nop2.426
|View full text |Cite
|
Sign up to set email alerts
|

Critical thinking skills of nursing students: Observations of classroom instructional activities

Abstract: Aim Critical thinking (CT) is vital for nursing practice. Nursing schools should provide learning experiences that enable nursing students to acquire CT skills. Yet, these authors are not aware of any study that has directly observed instructional activities related to CT skills acquisition in the classroom environment. The aim of this study was to explore instructional activities in the classroom environment in relation to acquisition of CT skills of students. Design Qualitative non‐participant observation. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 29 publications
(64 reference statements)
1
15
0
Order By: Relevance
“…The learner is the inquirer/discoverer of knowledge guided by the facilitator in an educational program. It was noted in this study that students were influenced by the Ghanaian cultural realities (Boso et al, 2020(Boso et al, , 2021c that did not allow them to question authority (Donkor & Andrews, 2011) and the type of assessment/teaching methods to which they are exposed. These authors posit that to assist in fostering CT skills of learners, the students should not see themselves as a receptacle in which content/information is dumped, but rather as rational individuals who can decide for themselves regarding truth.…”
Section: A Learner That Is Free To Question and Encouraged To Reflectmentioning
confidence: 87%
See 1 more Smart Citation
“…The learner is the inquirer/discoverer of knowledge guided by the facilitator in an educational program. It was noted in this study that students were influenced by the Ghanaian cultural realities (Boso et al, 2020(Boso et al, , 2021c that did not allow them to question authority (Donkor & Andrews, 2011) and the type of assessment/teaching methods to which they are exposed. These authors posit that to assist in fostering CT skills of learners, the students should not see themselves as a receptacle in which content/information is dumped, but rather as rational individuals who can decide for themselves regarding truth.…”
Section: A Learner That Is Free To Question and Encouraged To Reflectmentioning
confidence: 87%
“…This article is the concluding part of a larger project (see Boso et al, 2020Boso et al, , 2021aBoso et al, , 2021bBoso et al, , 2021c CI is one of the approaches embedded in PAR (Mash, 2014;Mash & Meulenberg-Buskens, 2001) and is used interchangeable with PAR in this article. PAR inter alia assists in problem solving (Hart & Bond, 1995;Mash, 2014), promotes organizational improvement (Hart & Bond, 1995), bridges the theory-practice gap (Mash, 2014;Rolfe, 1996) and allows users to be involved (Beresford, 2006).…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, students can have different perceptions about tutor performance if the student still follows online tutorials solely to complete the attendance schedule and get the best score. The nursing literature is full of studies showing that applying appropriate teaching strategies such as active learning improves students' CT scores (Boso et al, 2020). (Ahmad, 2017) revealed that one of the important tasks of managers or heads of departments towards lecturers is to assess the performance achieved whether it is good or still lacking, especially in assessing the performance of tutors in this PBL online tutorial process to evaluate the work performance of employees and lecturers and determine further policies.…”
Section: Discussionmentioning
confidence: 99%
“…Developing and stimulating HOTS and clinical competency in student nurses is crucial to everyday practice, as they equip them with the required skills to respond to and solve varied and complex real-life health problems within dynamic healthcare settings (Boso, Van Der Merwe & Gross 2021;Fukada 2018). Factors such as effective clinical learning environment, clinical experience, learning opportunities, motivation and theoretical knowledge are among the most important factors affecting clinical competency of nurses (Karami, Farokhzadian & Foroughameri 2017).…”
Section: Consequences Higher-order Thinking Skills and Clinical Compe...mentioning
confidence: 99%